2013
DOI: 10.1152/jn.00539.2012
|View full text |Cite
|
Sign up to set email alerts
|

Roles for substance P and gastrin-releasing peptide as neurotransmitters released by primary afferent pruriceptors

Abstract: Recent studies support roles for neurokinin-1 (NK-1) and gastrin-releasing peptide (GRP) receptor-expressing spinal neurons in itch. We presently investigated expression of substance P (SP) and GRP in pruritogen-responsive primary sensory neurons and roles for these neuropeptides in itch signaling. Responses of dorsal root ganglion (DRG) cells to various pruritogens were observed by calcium imaging. DRG cells were then processed for SP, GRP, and isolectin B-4 (IB4; a marker for nonpeptidergic neurons) immunofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 34 publications
9
35
0
Order By: Relevance
“…For example, it was recently reported that GRP antagonists would inhibit nonhistaminergic itch, but not that elicited by histamine, and that histamine responses at the H1 receptor on C-fibers were unique in requiring phospholipase Cb as an intracellular mediator. 1,13,42 In conclusion, the data presented here provide, for the first time, evidence that the mTORC1 signaling pathway regulates both histamine-dependent and histamine-independent itch. Together with our previous studies on the role of mTORC1 in pain, 9,18,30,31 this result may suggest that a subpopulation of P-mTOR-positive A-fibers may also be crucial for the full response to pruritic stimuli and therefore may underline the importance of the mTORC1 pathway in the regulation of homeostatic primary afferent functions such as pain and itch.…”
Section: Metformin As An Antipruritic Agentsupporting
confidence: 57%
“…For example, it was recently reported that GRP antagonists would inhibit nonhistaminergic itch, but not that elicited by histamine, and that histamine responses at the H1 receptor on C-fibers were unique in requiring phospholipase Cb as an intracellular mediator. 1,13,42 In conclusion, the data presented here provide, for the first time, evidence that the mTORC1 signaling pathway regulates both histamine-dependent and histamine-independent itch. Together with our previous studies on the role of mTORC1 in pain, 9,18,30,31 this result may suggest that a subpopulation of P-mTOR-positive A-fibers may also be crucial for the full response to pruritic stimuli and therefore may underline the importance of the mTORC1 pathway in the regulation of homeostatic primary afferent functions such as pain and itch.…”
Section: Metformin As An Antipruritic Agentsupporting
confidence: 57%
“…A majority of GRP immunopositive fibers in dorsal root ganglion (DRG) cells express SP, CGRP, and TRPV1 (31,32). A recent in vivo study demonstrated that SP, glutamate, and GRP each partially contributes to histamine-independent itch (33). Patch clamp recordings using slices of spinal cord from rats and mice revealed that a portion of dorsal horn neurons receiving input from PANs showed an increased firing frequency of action potential in response to GRP application (34).…”
Section: Tks and Itchmentioning
confidence: 99%
“…Histaminergic and non-histaminergic itch require TRPV1 and TRPA1, respectively [18; 33]. In the spinal cord, glutamate as well as neuropeptides including substance P, gastrin releasing peptide (GRP), neuromedin B, and natriuretic polypeptide B (Nppb) are involved in the transmission of itch signals [6; 8; 21; 27; 36]. Neurons expressing the substance P neurokinin-1 receptor (NK1R) represent the majority of ascending somatosensory projection neurons from the spinal and medullary dorsal horn, and are implicated in acute itch [14; 29].…”
Section: Introductionmentioning
confidence: 99%